PENYUSUNAN PETA RAWAN BANJIR SUNGAI SERAYU HILIR MENGGUNAKAN HEC-RAS DAN SISTEM INFORMASI GEOGRAFIS - , Sumarno ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In addition to providing benefit for human life, the area along the river also holds the potential of a pool that can be harmful and dangerous to humans. The inundation may caused by the overflowing water that fills the space on the right and left of the river due to discharge that exceeds the capacity of the river. This study is aimed at developing an inundation hazard map of lower reach of Serayu River for about 30 km, starting from the estuary up to downstream of the Bendung Gerak Serayu (Serayu Barrage) using GIS and HEC-RAS mathematical model. Delineation of boundaries around the river flood areas can be conducted using manual method by recording flood events that have occurred within a certain time or automatically by utilizing the software of hydrology, hydraulics and Geographic Information Systems (GIS). This automated method will increase the effectiveness of time, accuracy of flood discharge prediction and flood inundation area boundaries. In this study, HEC-RAS hydraulic models used for simulation of water surface profile at lower reach of Serayu River by utilizing design discharge data from hydrology analysis conducted by Serayu Opak River Basin Organization. Input data of stream geometry parameters for HEC-RAS was obtained from the analysis of digital terrain model (DTM) using GIS software (ArcGIS) with HECGeoRAS extension. The output of hydraulic analysis are water surface profile for 2 and 5 years return period of flood and flood hazard maps of Serayu River for each return period.